Active learning in online teaching in SMA Swakarya Binjai (Talenta Publisher, 2020)
Nowadays, the education world in learning method is not only using a conventional method, which is basically, by an explanation from a teacher and merely from the learning books. But, with an effective and efficient learning method, so that the students are able to keep up and participate actively during the lesson, by taking an advantage of IT (Information Technology), especially for facing the changes in learning due to pandemic COVID-19. The contribution from people is one of the ways to carry out the socialisation of information technology. This community service, will be implemented in this research entitled